Establishing Orbital Floor Symmetry to Support Mirror Imaging in Computer-Aided Reconstruction of the Orbital Floor. Issue 6 (September 2019) - Jozaghi, Yelda; Chan, Harley H.L.; Davies, Joel C.; Irish, Jonathan C.
Abstract : Background: Surgical precision in the reconstruction of the orbital floor is crucial to functional visual and aesthetic outcomes. Increasingly, computer-aided design is being utilized to aid in precise preoperative planning by using the mirror images of the unaffected side. The authors aim to use 3-dimensional (3D) quantitative analysis to establish whether the native orbital floor topography is sufficiently symmetric to support this practice. Methods: Ten high resolution head and neck computed tomography scans of patients without periorbital pathology were obtained. These were imported into a 3D medical image processing software and segmented to isolate bilateral orbital floors. Each native orbital floor was compared to the mirror image of the contralateral side by conformance map computation. Data collection included measures of 25% and 75% quartile, median, mean, standard deviation, and root-mean-square (RMS). Results: The topographic analysis demonstrated a high degree of topographic conformance with a mean RMS of 0.58 ± 0.37 mm. Further volumetric analysis comparing the total orbital volume between each side also demonstrates a high degree of volumetric symmetry with a mean difference of 0.55 mL ( P  = 0.30). Conclusion: Comparison of the native orbital floor and the mirror image of the contralateral side by conformance map computation and volumetric analysis demonstrated a high degree of morphologic similarity. The native orbital floor topography provides optimal symmetry to support mirror imaging techniques used in orbital floor reconstruction. Abstract : Supplemental Digital Content is available in the text